Data on the function of CDH17 in pancreatic cancer growth - Hao Yuan; Joseph Stenberg; Guangfu Li (Data in Brief, 2019)
Data presented in this article are related to the research article entitled “Disruption of oncogenic liver-intestine cadherin (CDH17) drives apoptotic pancreatic cancer death”. To investigate the influence of CDH17 on human pancreatic cancer (PC), we performed gain and loss of CDH17 function with siRNA and recombinant plasmid to evaluate its impact on PC cell proliferation, colony formation, and migration. The data can be valuable for researchers interested in the study of oncogenic activity related to the CDH17 gene in PC growth and motility. Keywords: Pancreatic cancer, CDH17, Tumorigenesis